Ein Brandhorizont aus der Zeit der Markomannenkriege im südostnorischen Munizipium Flavia Solva - Hinker, Christoph (Österreichisches Archäologisches Institut, 2014)
The publication provides a detailed study of a burnt layer from Insula XLI in Flavia Solva (Wagna, Austria), dated ca. AD 170, i.e. within the period of the Marcomannic Wars.